Relação entre a presença de periodontite apical crônica e os níveis de proteína C-reativa - VALOIS, Érica Martins (2010)
The correlation between chronic apical periodontitis and C-reactive protein levels. The aim of this study was to verify if the presence, number and size of apical periodontal lesions would influence C-reactive protein (CRP) levels. Forty-five subjects were selected from Ondonthology Clinics of Universidade Federal do Maranhão and Centro Universitário do Maranhão and studied according with existence of Chronic apical periodontitis, diagnosed by periapical radiography. CRP levels were measured during the same evaluation section, using Quickread CRP® (Orion Diagnostica, Ireland). CRP level cut off was 10mg/L. Q-square media test and logistic regression model (SPSS 17.0) were used to ensure if the presence, number and size of periapical lesions would significantly influence CRP levels. There were no correlation between the presence of lesions and CRP levels (x2 =0,556, P=0,456). There were also no significant correlation between the number (P=0,665) and size (P=0,698) of the lesions and CRP levels. This study concludes that the presence, number and size of periapical lesions do not influence CRP levels.